Comparative Assessment of Bioactive Compounds, Nutritive, Mineral Composition and In-Vitro Bioactivity of Marine Macro Algae Valoniopsis Pachynema and Dictyota Ciliolata: Life Sciences-Food science and nutrition - J, Bhuvaneshwari; Vasan.P, Thirumalai (International Journal of Life Science and Pharma Research, 2022)
Marine-based nutraceuticals have proved their extensive applications in functional foods and its bioactive molecules play a crucial role as therapeutic agents. The aim of the study is to elucidate in-depth understanding of the nutritional properties and biological activities of the two marine algae. The main objectives of the current study is to comparatively analyse the phytochemicals, nutritional composition and its pharmacological activities of the green and the brown marine macro algae named V.pachynema and D.ciliolata respectively using three different solvents. Additionally, the total chlorophyll content, phenolic content, nutritional, mineral composition, antioxidative and antibacterial activities of the methanolic extract were evaluated. Results showed elemental distribution of V.pachynema in the decreasing order Na > Ca> k > Mg > Fe > Ni> Mn >Co> As > Pb > Cu> Zn > Cr > Cd> Se> V while D.ciliolata in the order of Na > Ca> k > Mg >Ni >Fe> As> Co >Pb> Mn > Zn> Se>Cr> Cd> V>Cu. The relative nutritional composition showed high ash and carbohydrate for both the algae. The percentage composition of ash content was 68.42 ± 0.43% , 37.45 ± 0.26 % (g 100g-1 DW) while carbohydrate content was 50.17± 0.60%, 45.78 ± 0.69% (g 100g-1 DW) for V.pachynema and D.ciliolata respectively. The crude methanolic extract of both the algae were investigated for antioxidant activity with two in vitro antioxidant assays including 1,1-diphenyl-2- picrylhydrazyl radical (DPPH), Phosphomolybdenum (PMB) assays. In addition, Folin–Ciocalteu was used to measure phenolic content (TPC) to determine the antioxidant components. Total phenolic content was found to be highest in V.pachynema 51 GAE 10µg/ml and the methanolic extract of V.pachynema showed higher levels of phenolic compounds and antioxidant activities when compared with D.ciliolata. The tested marine algal extracts exhibited radical scavenging activity that is comparatively dose-dependent to its phenolic concentration. Methanolic extract of the marine algae V.pachynema exhibited better inhibitory activity against gram positive bacterium that are resistant to drugs when compared to the brown algae D.ciliolata. This study enabled a detailed understanding of the nutritional and biochemical composition, free radical scavenging activities of two marine macroalgae. This algal biomass could be potent resources of anti-oxidants and could act as dietary food supplements owing to their rich diversified bioactivities.